2006
DOI: 10.1007/s10479-006-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal asset allocation for pension funds under mortality risk during the accumulation and decumulation phases

Abstract: In a financial market with one riskless asset and n risky assets whose prices are lognormal, we solve in a closed form the problem of a pension fund maximizing the expected CRRA utility of its surplus till the (stochastic) death time of a representative agent. We consider a unique asset allocation problem for both accumulation and decumulation phases. The optimal investment in the risky assets must decrease during the first phase and increase during the second one. We accordingly suggest it is not optimal to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Regarding demographic factors, we recall that in a constant interest rate framework the mortality risk has been taken into consideration by [Battocchio, Menoncin & Scaillet, 2007].…”
Section: The Related Literature On Pension Funds Management and On Thmentioning
confidence: 99%
“…Regarding demographic factors, we recall that in a constant interest rate framework the mortality risk has been taken into consideration by [Battocchio, Menoncin & Scaillet, 2007].…”
Section: The Related Literature On Pension Funds Management and On Thmentioning
confidence: 99%
“…For example, Haberman and Sung [2] try to minimize the 'solvency' and 'contribution rate' risks in order to stabilize the pension fund, and Cairns et al try to optimize the terminal utility gained from the pension fund with a stochastic interest rate [3]. Some other examples of the studies that deal with the optimal asset allocations for pension funds can be found in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. On the other hand, there are limited numbers of studies that consider a target or a guaranteed wealth concept.…”
Section: Introductionmentioning
confidence: 99%
“…Haberman and Vigna (2001) consider downside risk of an optimal asset allocation strategy derived from a discrete-time dynamic programming approach. Salary risk and inflation risk were incorporated in Battocchio and Menoncin (2004) and Han and Hung (2012) while maximizing the expected utility of terminal wealth. Battocchio, Menoncin, and Scaillet (2004) and Yang and Huang (2009) incorporate longevity risk in the optimal asset allocation of a DC plan; the former using as objective expected utility, and the latter deviation of terminal wealth with respect to a predetermined target.…”
Section: Introductionmentioning
confidence: 99%
“…Salary risk and inflation risk were incorporated in Battocchio and Menoncin (2004) and Han and Hung (2012) while maximizing the expected utility of terminal wealth. Battocchio, Menoncin, and Scaillet (2004) and Yang and Huang (2009) incorporate longevity risk in the optimal asset allocation of a DC plan; the former using as objective expected utility, and the latter deviation of terminal wealth with respect to a predetermined target. Stochastic lifestyling under terminal utility with habit formation is found and compared with other strategies in Cairns, Blake, and Dowd (2006).…”
Section: Introductionmentioning
confidence: 99%